Difficulty in the diagnosis of bone and joint pain associated with pediatric acute leukemia; comparison with juvenile idiopathic arthritis. Issue 1 (2nd January 2018) - Tsujioka, Takao; Sugiyama, Minako; Ueki, Masahiro; Tozawa, Yusuke; Takezaki, Shunichiro; Ohshima, Junjiro; Cho, Yuko; Yamada, Masafumi; Iguchi, Akihiro; Kobayashi, Ichiro; Ariga, Tadashi
Abstract: Objectives: Acute leukemia often causes osteoarthralgia. The aim of this study is characterization of leukemia-associated osteoarthralgia in comparison with juvenile idiopathic arthritis (JIA). Methods: We retrospectively reviewed clinical records of 31 patients with acute leukemia and 13 patients with articular JIA diagnosed between January 2008 and March 2013. Clinical and laboratory findings at the initial examination were compared among the three groups; 10 leukemia with and 21 leukemia without osteoarthralgia and 13 JIA groups. Results: Eleven of the 31 leukemic patients (35%) had osteoarthralgia before the diagnosis of leukemia. Peripheral leukemic cells were initially absent in 10 of the 31 leukemia patients including three with osteoarthralgia. Platelet counts over 300 × 10 9 /L were common in JIA, but not in osteoarthralgia group. Mean serum lactate dehydrogenase levels were higher in both of the leukemia groups than JIA group but often within normal or near-normal levels in the leukemia groups. Magnetic resonance imaging was examined in three leukemic patients and demonstrated osteomyelitis-like bone marrow edema in two and periarticular infiltration similar to synovitis in one patient. Three leukemic patients with osteoarthralgia showed partial and transient responses to antibiotic therapy. Conclusions: Leukemia-associated osteoarthralgia is often indistinguishable from rheumatic diseases by imaging and laboratory findings and should be confirmed by bone marrow examination.